Pensión 65 y su incidencia en la pobreza de La Libertad, 2000 - 2021 - Flores Lopez, Mia Isolina (2022)
This thesis study aimed to establish the impact of the National Program of Solidarity Assistance Pension 65 affects the poverty of the La Libertad Region, during the period 2000 - 2021, based theoretically on the theory of old age as a minority group and life cycle theory primarily. The methodological design was nonexperimental, longitudinal and explanatory. Data were mainly obtained from the portal of the Ministry of Economy and Finance (MEF), the portal of the Ministry of Development and Social Inclusion (MIDIS), the National Institute of Statistics and Informatics (INEI), the Operational Monitoring and Monitoring System (SOSEM); and, from the Regional Information System (SIR) A model of Ordinary Least Squares was developed, where the dependent variable was the poverty of the elderly and as an independent variable was the pension program 65 (coverage and population). The main result is that the national pension 65 solidarity assistance programme has a positive impact on the poverty of the elderly in the La Libertad region. The final model determined is: poverty=-867.78-15.81*coverage+65.783*lpopulation